1999
DOI: 10.1055/s-1999-14234
|View full text |Cite
|
Sign up to set email alerts
|

Chest Ultrasound in Diagnosis of Pulmonary Embolism in Comparison to Helical CT

Abstract: CUS can improve diagnosis of pulmonary embolism. Sonography also reveals small infarcts which remain undetected with other imaging procedure such as helical CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 0 publications
1
36
0
7
Order By: Relevance
“…Although the sonographic accuracy was more than 90%, these reports appear to have been overlooked for many years. More recently, several investigators have confirmed the original results [22, 23]. Since PE is a potentially fatal disease needing rapid onset of therapy, alternative easily accessible methods available to the physician at bedside may facilitate a swift diagnosis of PE.…”
Section: Introductionmentioning
confidence: 78%
“…Although the sonographic accuracy was more than 90%, these reports appear to have been overlooked for many years. More recently, several investigators have confirmed the original results [22, 23]. Since PE is a potentially fatal disease needing rapid onset of therapy, alternative easily accessible methods available to the physician at bedside may facilitate a swift diagnosis of PE.…”
Section: Introductionmentioning
confidence: 78%
“…Lung parenchymal lesions due to embolism have some particular sonographic characteristics, and most of them are localized in an area of pleuritic chest pain (6 -8). Similar hypoechoic images are present in some other diseases of the lung, and false-positive chest ultrasound may derive from other peripheral consolidations of the lung, especially pneumonic or neoplastic infiltrates (7,8). In a recent study, Mohn and colleagues found some disappointing results about the accuracy of lung ultrasound in excluding or confirming pulmonary embolism (14).…”
Section: Discussionmentioning
confidence: 94%
“…Pleuritic pain is the most frequent presenting symptom of pulmonary embolism, but the latter is a condition that affects only a minority of patients admitted to the ED for the evaluation of thoracic pain (1)(2)(3)13). We know from literature review that lung ultrasound may be useful in the diagnosis of pulmonary embolism (5)(6)(7)(8). All these articles describe some parenchymal findings at lung ultrasound that are considered typical of peripheral lung infarct due to embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charakteristische Verän-derungen sind ein bzw. typischerweise mehrere dreieckförmige, echoarme, intrapulmonal gelegene und meist glatt begrenzte Herde mit subpleuraler Basis und gelegentlich darstellbarem zentralen Bronchusreflex [104,135,136]. Daneben findet sich häufig ein zum Infarktbereich korrespondierender, umschriebener und bei größerer Ausdehnung auch ein basaler Pleuraerguss.…”
Section: Anwendung Der Konsensusklassifikationunclassified